Dispersion as an important step in the Candida albicans biofilm developmental cycle. - Priya Uppuluri (PLoS Pathogens, 2010)
Biofilms are dynamic microbial communities in which transitions between planktonic and sessile modes of growth occur interchangeably in response to different environmental cues. In the last decade, early events associated with C. albicans biofilm formation have received considerable attention. However, very little is known about C. albicans biofilm dispersion or the mechanisms and signals that trigger it. This is important because it is precisely C. albicans cells dispersed from biofilms that are the main culprits associated with candidemia and establishment of disseminated invasive disease, two of the gravest forms of candidiasis. Using a simple flow biofilm model recently developed by our group, we have performed initial investigations into the phenomenon of C. albicans biofilm dispersion, as well as the phenotypic characteristics associated with dispersed cells. Our results indicate that C. albicans biofilm dispersion is dependent on growing conditions, including carbon source and pH of the media used for biofilm development. C. albicans dispersed cells are mostly in the yeast form and display distinct phenotypic properties compared to their planktonic counterparts, including enhanced adherence, filamentation, biofilm formation and, perhaps most importantly, increased pathogenicity in a murine model of hematogenously disseminated candidiasis, thus indicating that dispersed cells are armed with a complete arsenal of "virulence factors" important for seeding and establishing new foci of infection. In addition, utilizing genetically engineered strains of C. albicans (tetO-UME6 and tetO-PES1) we demonstrate that C. albicans biofilm dispersion can be regulated by manipulating levels of expression of these key genes, further supporting the evidence for a strong link between biofilms and morphogenetic conversions at different stages of the C. albicans biofilm developmental cycle. Overall, our results offer novel and important insight into the phenomenon of C. albicans biofilm dispersion, a key part of the biofilm developmental cycle, and provide the basis for its more detailed analysis.